Linguistically and culturally relevant education on the roof of the world: The collaborative creation of a Ladakhi storybook. Issue 1 (1st August 2019) - Dowd, Patrick
This article describes the creation of a culturally and linguistically relevant storybook written for 10–12-year-old children in the Ladakh, a high-altitude region of the Indian Himalayas. Formerly a part of the Tibetan Empire, Ladakh came under Indian rule in the mid-nineteenth century but maintained strong autonomy and close ties with its neighbour to the north until China closed the Ladakh-Tibet border in the late 1950s. In the 1970s the Indian government opened the Ladakh to tourism which resulted in rapid change, transforming the preindustrial, largely agrarian society into one heavily dependent on tourism. In a region where the total population is less than 275, 000, in 2016 alone nearly 240, 000 tourists visited Ladakh, almost 200, 000 of whom were Indian. Language shift from Ladakhi to Hindi and English, as well as a profound sense of cultural alienation, are among the unintended consequences of the tourist industry and thorough incorporation of Ladakh into the Indian market economy.Having interviewed numerous teachers, principals, and education activists in the summer of 2016, they nearly unanimously argued that the lack of culturally relevant, Ladakhi-centric material was a major reason young Ladakhis failed to learn their language well and the cultural values embedded within it. I returned to Ladakh in August 2017 to work with a team of local Ladakhi university students, writers and illustrators to produce a children's storybook rooted in the people, landscape, language and culture of Ladakh. 1, 000 copies were printed in February 2018 and are currently being distributed in Ladakh by the Himalayan Cultural Heritage Foundation. The article describes the collaborative research, writing and illustration that produced the book, as well as how we navigated the delicate balance of honouring colloquial Ladakhi while still respecting the grammar and spelling of the literary Tibetan language on which it is based.